Pentingnya Pendidikan Multikultural Berbasis Agama - Rizki, Oki Fitrian (Institut Teknologi Pendidikan Indonesia, 2023)
In this article, the author wants to see how important multicultural education is, especially inreligion-based development. Interestingly, Islamic education must be able to consider multicultural education as an indicator of realizing the goals of Islamic education. This study uses a literature study research method. The data used in this study uses secondary data in the form of research results such as books, journals, articles, and other relevant sources. Data analysis techniques in this study used content analysis data analysis techniques. The results of this study indicate that multicultural Islamic education can be used as a new approach to changing people's ways of thinking and perspectives, as well as attitudes and behavior skills in a pluralistic life. In this context, multicultural Islamic education offers a spirit of religious life based on peace, tolerance, respect for diversity, and other attitudes that support human values and the spirit of Indonesian unity.